1979
DOI: 10.3758/bf03326644
|View full text |Cite
|
Sign up to set email alerts
|

Salt seeking by means of food and fluid selection in adrenalectomized rats

Abstract: An experiment involving several changes in the salt content of food and solutions investigated the generality of salt-seeking behavior in adrenalectomized rats. Salt-solution intake varied as a function of NaCI concentration. The intake of sodium is relatively unaffected by the concentration of NaCI in the food as long as NaCI in solution is available. But when the salt solution is removed, salt seekingand sodium regulation takes placeby way of salt in the food.It has been demonstrated repeatedly that rats dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…These studies support and extend previous work showing that adrenalectomy (Grimsley & Starnes, 1979) or maintenance on a sodium-deficient diet (Rodgers, 1967) can produce preferences for salted food. It has been suggested that in evolutionary history, sodium deficiency placed selection pressure on the development of many vertebrate species (Denton, 1982, p. 12).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…These studies support and extend previous work showing that adrenalectomy (Grimsley & Starnes, 1979) or maintenance on a sodium-deficient diet (Rodgers, 1967) can produce preferences for salted food. It has been suggested that in evolutionary history, sodium deficiency placed selection pressure on the development of many vertebrate species (Denton, 1982, p. 12).…”
Section: Discussionsupporting
confidence: 89%
“…Although there is less evidence, it appears that similar results can be obtained when food is the source of salt. For example, after adrenalectomy, rats prefer food containing added salt to food with no added salt (Grimsley & Starnes, 1979). Also, extended maintenance on a sodium-deficient diet can produce a mild, transient preference for salted food (Rodgers, 1967).…”
mentioning
confidence: 99%
“…Grimsley (1973) showed that adrenalectomized (ADX) rats would consume enough of a salt-enriched food to maintain body weight and to prevent the symptoms characterisitic of adrenal insufficiency. But given a choice between salt in food and in solution, the ADX animals showed a marked preference to regulate salt balance by drinking (Grimsley & Starnes, 1979).Ordinarily, rats without a salt deficiency will not prefer a salty food over a plain food. This has been shown with lab chow (Grimsley, 1973), and with a variety of other foods, including potato chips, peanuts, and soup (Beauchamp & Bertino, 1985).…”
mentioning
confidence: 99%
“…Grimsley (1973) showed that adrenalectomized (ADX) rats would consume enough of a salt-enriched food to maintain body weight and to prevent the symptoms characterisitic of adrenal insufficiency. But given a choice between salt in food and in solution, the ADX animals showed a marked preference to regulate salt balance by drinking (Grimsley & Starnes, 1979).…”
mentioning
confidence: 99%
See 1 more Smart Citation